Effect of age and aortic valve anatomy on calcification and haemodynamic severity of aortic stenosis. Issue 1 (8th August 2016) - Shen, Mylène; Tastet, Lionel; Capoulade, Romain; Larose, Éric; Bédard, Élisabeth; Arsenault, Marie; Chetaille, Philippe; Dumesnil, Jean G; Mathieu, Patrick; Clavel, Marie-Annick; Pibarot, Philippe
Abstract : Objective: To evaluate the effect of age and aortic valve anatomy (tricuspid (TAV) vs bicuspid (BAV) aortic valve) on the relationship between the aortic valve calcification (AVC) and the haemodynamic parameters of aortic stenosis (AS) severity. Methods: Two hundred patients with AS and preserved left ventricular ejection fraction were prospectively recruited in the PROGRESSA (Metabolic Determinants of the Progression of Aortic Stenosis) study and underwent a comprehensive Doppler echocardiography and multidetector CT (MDCT). Mean transvalvular gradient (MG) measured by Doppler echocardiography was used to assess AS haemodynamic severity and AVC was evaluated by MDCT using the Agatston method and indexed to the left ventricular outflow tract area to obtain AVC density (AVCd). All analyses were adjusted for sex. Results: Thirty-nine patients had a BAV and 161 a TAV. Median age was 51 and 72 years for BAV and TAV patients, respectively. There was a modest correlation between MG and AVCd (ρ=0.51, p<0.0001) in the whole cohort. After dichotomisation for valve anatomy, there was a good correlation between AVCd and MG in the TAV group (ρ=0.61, p<0.0001) but weak correlation in the BAV group (ρ=0.32, p=0.046). In the TAV group, the strength of the AVCd–MG correlation was similar in younger (<72 years old; ρ=0.59, p<0.0001) versus older (≥72 years old; ρ=0.61, p<0.0001) patients. In the BAV group, there was no correlation between AVCd and MG in younger patients (<51 years old; ρ=0.12, p=0.65), whereas there was a good correlation in older patients (≥51 years old; ρ=0.55, p=0.009). AVCd (p=0.005) and age (p=0.02) were both independent determinants of MG in BAV patients while AVCd (p<0.0001) was the only independent determinant of MG in TAV patients. Conclusions: In patients with TAV as well as in older patients with BAV, AVCd appears to be the main factor significantly associated with the haemodynamic severity of AS and so it may be used to corroborate AS severity in case of uncertain or discordant findings at echocardiography. However, among younger patients with BAV, some may have a haemodynamically significant stenosis with minimal AVCd. The results of MDCT AVCd should thus be interpreted cautiously in this subset of patients. Trial registration number: NCT01679431; Pre-results.